Монументальна пластика в зодчестві Києва XII ст. - Архипова, Є.І. (Археологія, 1997)
Розвиток кам'яної пластики давнього Києва обмежують кінцем X—XI ст. Критичний аналіз цієї точки зору і вивчення походження та стилістичних особливостей поки що невеликої групи пам'яток з фігурними зображеннями дозволяє розширити ці хронологічні межі. Про використання різьбленого каміння в декорі київських будівель XII ст. свідчить і нова знахідка різьбленої колонки з пісковику. По топографии находок памятники монументальной скульптуры древнего Киева датируют концом X—XI ст. К этому же времени относят и рельефы с фигурными изображениями, происхождение которых не установлено. Анализ стилистических особенностей произведений киевской сюжетной пластики и уточнение происхождения некоторых из них, позволили сделать вывод, что этот вид резьбы получает развитие в киевском зодчестве с конца XI — первой трети XII в. Рельефами с фигурными изображениями украшали как фасады, так и интерьеры зданий. Особой популярностью пользовалась змееборческая тема и преобладали сюжеты с изображениями животных (львы, грифон, овца (?). Развиваясь в русле западноевропейского искусства, киевская сюжетная пластика в целом была ориентирована на византийские образцы, однако отдельные памятники (в том числе новая находка резной колонки из песчаника) указывают, что в XII — начале XIII в. имели место романские заимствования. Памятники киевской орнаментальной резьбы XII в. пока трудно выделить в общем массиве находок, поскольку атрибуция их требует специального исследования. The topography of findings permits monumental sculpture relics of ancient Kiev to be dated the late 10th and 11th cent. Reliefs with figured patterns of undetermined origin are attributed to that time as well. The analysis of the stylistic properties of the Kiev plastic artworks and specification of the origin of some of them have permitted concluding that this type of carving was developed in the architecture of Kiev from the end of the 11th till the first third of the 12th cent. Reliefs with carved patterns decorated both the fronts of buildings and their interiors. The subjects showing the Warrior Saints killing dragons or depicting animals (lions, a gryphon, a sheep (?) were very popular. Developing in terms of Western-European art, the Kyiv plastic art in general was oriented to the Byzantine specimens, but some artifacts, including the new finding of a carved column made of sandstone, show that there were Roman borrowings in the 12th and early 13th cent. It is still difficult to identify relics of the Kiev ornamental carving of the 12th cent, among other findings, as their attribution demands particular study.